2010 13th IEEE International Conference on Computational Science and Engineering 2010
DOI: 10.1109/cse.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Academic Conference Classification Using Social Tags

Abstract: Abstract-Automatically classifying academic conference into semantic topic promises improved academic search and browsing for users. Social tagging is an increasingly popular way of describing the topic of academic conference. However, no attention has been devoted to academic conference classification by making use of social tags. Motivated by this observation, this paper proposes a method which utilizes social tags as well as the content of academic conference in order to improve automatically identifying ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Hurtado Martin et al proposed an approach based on user profiles, which takes a scholar's recent publication list and recommends related CfPs using content analysis [3]. Xia et al presented a classification method to filter CfPs by social tagging [10]. Wang et al proposed another approach to classify CfPs by implementing three different methods but focus on comparing the classification methods rather than services to improve scientific communication [9].…”
Section: Related Workmentioning
confidence: 99%
“…Hurtado Martin et al proposed an approach based on user profiles, which takes a scholar's recent publication list and recommends related CfPs using content analysis [3]. Xia et al presented a classification method to filter CfPs by social tagging [10]. Wang et al proposed another approach to classify CfPs by implementing three different methods but focus on comparing the classification methods rather than services to improve scientific communication [9].…”
Section: Related Workmentioning
confidence: 99%
“…Also, they conclude that the more users annotate a URL, the better it is classified. Xia et al [33] studied the usefulness of social tags as a complementary source for improving the classification of academic conferences into topics. Using tagging data gathered from WikiCFP.com, and weighting the tags according to the number of users using them, they compare the classification of conferences by using only the content of the call for papers, and by integrating tagging data along with it.…”
Section: Related Workmentioning
confidence: 99%
“…There are others trying to address this problem by improving CFP retrieval performance. Xia et al [4] proposed the use of social tags in CFP classification to increase the accuracy. Issertial and Tsuji [5] showed that adding enriched ontology into structure data of CFPs will increase the recall in CFP retrieval.…”
Section: Introductionmentioning
confidence: 99%